IoT as Non-Pharmaceutical Interventions for the Safety of Living Environments in COVID-19 Pandemic Age - Gamberini, Luciano; Pluchino, Patrik; Bacchin, Davide; Zanella, Andrea; Orso, Valeria; Anna, Spagnolli; Mapelli, Daniela (Frontiers in Computer Science, 2021)
The outbreak of the Sars-Cov-2 pandemic has changed our perception of safety in shared and public living environments including healthcare facilities, shops, schools, and enterprises. The Internet of Things (IoT) represents a suitable solution for managing anti-pandemic smart devices (e.g., UV lights, smart cameras, etc.) and increasing citizens’ safety in public health crises. In this paper, we present SAFE PLACE, a project meant to design and develop an IoT system to ensure the safety of shared environments. Advanced algorithms will be exploited to detect and classify humans' presence, gathering, usage of personal protective equipment, and considering carefully the privacy protection of individuals.